A Rare Case of Meningitis Caused by Alcaligenes faecalis in an Immunocompetent Patient - Kevin Cantillo García; Oscar Calderón Duran; Tomás Acosta Pérez; Ángel Vásquez Jiménez; Emerson Madrid Pérez; María Cristina Martínez-Ávila; Tomás Rodríguez Yánez; Amilkar Almanza-Hurtado (Case Reports in Medicine)
Alcaligenes faecalis (A. faecalis) is a Gram-negative rod rarely isolated as an infective bacterium worldwide. The first cases of infections caused by this microorganism, such as pneumonia, soft tissue infections, urinary tract infections, bacteremia, and meningitis, date back more than 40 years and are almost entirely in newborns and immunosuppressed hosts. Optimal antibiotic therapy for A. faecalis has not been well established in the literature. We report a case of an immunocompetent patient in Colombia who had meningitis due to A. faecalis after a dental procedure. It is important to know about this microorganism that nowadays could be considered a potentially emerging pathogen in immunocompetent adults.